Plasticity-enhanced lead lanthanum zirconate tin titanate-based antiferroelectric ceramic and preparation method thereof

Through flash firing technology and strontium element doping, the zirconium tin lead lanthanum-titanate antiferroelectric ceramic material prepared has solved the crack problem caused by volume strain of antiferroelectric ceramics under high electric field, extended the charge and discharge life and improved the Energy storage density and efficiency.

CN119118662AActive Publication Date: 2024-12-13SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411167311.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-13
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

Antiferroelectric ceramic materials are prone to cracks and failures due to volume strain under high electric fields, and have short charge and discharge life. The prior art extends the life by reducing the working electric field but sacrifices energy storage density.

Method used

Zirconium tin lead titanate-based antiferroelectric ceramics prepared by flash firing technology, which reduces grain size, increases the number of dislocations, and relieves local stress through antiferroelectric-ferroelectric phase transition induced by strontium element doping and electric field. Improve the plasticity of the material.

Benefits of technology

It extends the charge and discharge life, improves the energy storage density and energy storage efficiency, reduces dielectric loss, and realizes the plasticity enhancement of ceramics and the gradient regulation of component structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118662A_ABST
    Figure CN119118662A_ABST
Patent Text Reader

Abstract

The invention relates to plasticity-enhanced lead lanthanum zirconium tin titanate-based antiferroelectric ceramic and a preparation method thereof. The chemical formula of the zirconium tin lead titanate lanthanum-based anti-ferroelectric ceramic is (Pb < 0.975-x > La < 0.02 > Sr < x >) (Zr < 0.5 > Sn < 0.37 > Ti < 0.13 >) < 0.9975 > O < 3 >, x is smaller than or equal to 0.10; and sintering by adopting a flash sintering technology to prepare the plasticity-enhanced lead lanthanum zirconate tin titanate-based antiferroelectric ceramic. Wherein the initial electric field intensity is set to be 100-300 V / cm, and the temperature rise rate of the flash sintering furnace body is 5-15 DEG C / min; when the reading of the current detector reaches the order of magnitude of [mu] A, the electric field intensity is increased to 200-500V / cm; after the current density value reaches 10-30 mA / mm < 2 >, the stable current density is kept for 90-200 s; preferably, the temperature rise rate of the flash burning furnace body is 8-12 DEG C / min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional material research and technology development, and specifically relates to a plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic material and a preparation method thereof. Background Art

[0002] As the energy storage element of pulse power supply, capacitors account for a large proportion of the entire energy storage device and are extremely important key components. Improving the energy storage density of capacitors plays an important role in increasing the power of pulse power supply, reducing the weight and volume of equipment, and meeting the development of miniaturization and high power. Therefore, the development of high-performance pulse capacitors has become a research focus and urgent task in the field of current pulse power technology.

[0003] Compared with linear dielectric materials and ferroelectric materials, antiferroelectric materials have the advantages of high energy storage density and fast charging and discharging, and have become a very important candidate material in the current application of high-performance pulse capacitors and are highly favored. High-performance antiferroelectric multilayer capacitors are one of the key directions for the future development of pulse power capacitors at home and abroad. They can meet the development requirements of miniaturization and high power of components, but there are high technical barriers.

[0004] The antiferroelectric-ferroelectric phase transition of antiferroelectric materials brings high energy storage but also accompanies large volume strain (~0.5%). When large volume changes occur within nanoseconds, large internal stress will be generated inside the ceramic, which will easily cause cracks to initiate and expand quickly, resulting in ceramic breakdown and failure, leading to short charge and discharge life. At present, the main way to extend the charge and discharge life is to reduce the working electric field (~ turning electric field) and sacrifice part of the energy storage density, but the advantage of high energy storage density has not been fully utilized. Summary of the invention

[0005] In view of the above problems, the present invention aims to provide a lanthanum zirconium tin titanate lead based antiferroelectric ceramic with enhanced plasticity and a preparation method thereof. The lanthanum zirconium tin titanate lead based ceramic material prepared by the present invention has a moderate Curie temperature, improved plasticity and dislocation density, and thus can achieve a prolonged charge and discharge life.

[0006] In one aspect, the present invention provides a plasticity-enhanced zirconium tin titanate lead lanthanum-based antiferroelectric ceramic, wherein the chemical formula of the zirconium tin titanate lead lanthanum-based antiferroelectric ceramic is (Pb 0.975-x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975O3, where 0 < x ≤ 0.10; the plastically enhanced lead lanthanum zirconate titanate antiferroelectric ceramic is prepared by flash sintering; wherein, the initial electric field strength is set to be 100 - 300 V / cm, and the heating rate of the flash sintering furnace body is 5 - 15 °C / min; when the reading of the current detector reaches the μA level, the electric field strength is increased to 200 - 500 V / cm; when the current density value reaches 10 - 30 mA / mm 2 After that, maintain a stable current density for 90 - 200 s; preferably, the heating rate of the flash sintering furnace body is 8 - 12 °C / min.

[0007] The present invention uses the flash sintering technology for the first time to prepare the plastically enhanced lead lanthanum zirconate titanate antiferroelectric ceramic. Antiferroelectric materials mainly store energy by means of the electric field-induced antiferroelectric-ferroelectric phase transition. However, in addition to generating a high energy storage density, the phase transition is also accompanied by a large volume strain (~0.4%) due to the difference in unit cells. When such a large volume change occurs in the ceramic within nanoseconds, it will generate a great local stress, seriously damaging the internal structure of the ceramic, and cracking and failure are likely to occur after multiple charge and discharge cycles. Therefore, the short charge and discharge life is the main bottleneck that has always prevented the widespread application of antiferroelectric materials. Previous studies have found that there are a large number of dislocations in the PbZrO3-based antiferroelectric ceramic, and they are closely related to the grain size. The flash sintering of the present invention can significantly reduce the grain size and increase the number of dislocations. The stress field and internal electric field around the dislocations will affect the crack propagation mode, and can climb and decompose under the action of stress. Therefore, the local stress can be successfully relieved through dislocation slip or dislocation emission, reducing the average hardness and modulus of the sample, improving the plasticity of the sample, thereby inhibiting crack initiation and propagation, and achieving the extension of the charge and discharge life.

[0008] Preferably, 0.016 ≤ x ≤ 0.064.

[0009] Preferably, the average hardness of the lead lanthanum zirconate titanate antiferroelectric ceramic is 6 - 7 MPa; the average modulus of the lead lanthanum zirconate titanate antiferroelectric ceramic is 160 - 175 MPa.

[0010] The present invention uses lead lanthanum zirconate titanate ceramic as the matrix material. Through strontium doping, the material is transformed from the initial ferroelectric phase to the antiferroelectric phase, and with the increase of the strontium doping amount, the electric hysteresis of the antiferroelectric material gradually decreases.

[0011] On the other hand, the present invention provides a method for preparing a plastically enhanced lead lanthanum zirconate titanate antiferroelectric ceramic, including: (1) Using Pb3O4 powder, La2O3 powder, SrCO3 powder, ZrO2 powder, TiO2 powder, SnO2 powder as raw materials, according to the chemical formula (Pb 0.975-x La 0.02 Sr x )(Zr0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3 is weighed and mixed, ball-milled and dried to obtain a first ceramic powder; (2) pressing the obtained ceramic powder into blocks, and calcining to obtain ceramic blocks; (3) grinding and crushing the obtained ceramic block, performing secondary ball milling, drying, and screening, adding a binder to granulate, and pressing to obtain a ceramic body; aging the obtained ceramic body, and then performing secondary grinding and crushing to obtain a second ceramic powder; (4) taking an appropriate amount of the second ceramic powder and pressing and molding it to obtain a first green blank; sealing the obtained first green blank and then cold isostatically pressing and removing the plastic to obtain a second green blank; (5) The plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic is prepared by sintering using a flash sintering technique.

[0012] Preferably, in step (1), the ball milling is performed by wet ball milling, with zirconium oxide balls as the ball milling medium and deionized water / anhydrous ethanol as the ball milling agent, and the ball milling is performed in a ratio of mixed powder: zirconium oxide balls: water / anhydrous ethanol of 1: (3.5-5): (1.2-1.5), the ball milling speed is 120-180 r / min, and the ball milling time is 8-12 h.

[0013] Preferably, in step (2), the pressure for pressing into blocks is 100-300 MPa, and the time is 5-30 seconds; The calcination temperature is 800-900° C., the calcination time is 2-4 hours, and the ambient atmosphere is air.

[0014] Preferably, in step (3), the secondary ball milling is performed by wet ball milling, using zirconium oxide balls as the ball milling medium and deionized water / anhydrous ethanol as the ball milling agent, and the ball milling is performed in a ratio of mixed powder: zirconium oxide balls: water / anhydrous ethanol of 1: (3.5-5): (1.2-1.5), the ball milling speed is 120-180 r / min, and the ball milling time is 18-24 h.

[0015] Preferably, in step (3), the binder is at least one of PVA and PVB; the concentration of the binder is 5 to 10 wt%; and the amount of the binder added is 5 to 8 wt% of the mass of the sieved ceramic powder.

[0016] Preferably, in step (3), the aging temperature is room temperature and the aging time is 18 to 24 hours.

[0017] Preferably, in step (4), the mass of the second ceramic powder is 2.5 to 3.2 g.

[0018] Preferably, in step (4), the pressure of the pressing molding is 50 to 200 MPa and the time is 3 to 10 s; The cold isostatic pressing pressure is 200-300 MPa and the time is 3-5 min; The temperature of the plastic removal is 650-800°C and the time is 2-3h; Preferably, the first blank is cylindrical, with a diameter of 6 mm and a length of 1.6-2.4 cm.

[0019] Preferably, in step (5), the flash burning technique comprises: Silver-palladium conductive paste is uniformly coated on both end regions of the obtained second blank, and after drying at 100-120° C., platinum wire is respectively wound around both end regions of the second blank coated with electrodes, and placed in a flash furnace; preferably, the width of the silver-palladium conductive paste coated on both end regions of the second blank is 3-5 mm; Connect the two ends of the platinum wire to the positive and negative electrodes of the DC power supply outside the furnace, and connect an ammeter in series in the circuit; First, the DC power supply adopts a voltage control mode, the initial electric field strength is set to 100-300 V / cm, and the furnace heating rate is set to 5-15°C / min; preferably, the initial electric field strength is 100-150 V / cm, and the furnace heating rate is set to 8-12°C / min; When the current detector reading reaches the μA level, increase the electric field strength to 200-500 V / cm; When the current density reaches 10~30mA / mm 2 After that, switch the DC power supply to current control mode; After maintaining a stable current density for 90 to 200 seconds in the current control mode, the DC power switch is turned off, and the flash furnace is taken out after being cooled to room temperature to obtain the plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic.

[0020] Preferably, the preparation method further comprises: cutting the obtained plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic and sputtering it with silver and gold electrodes.

[0021] In the present invention, operations such as granulation and isostatic pressing of the powder ensure that the green body of the flash-sintered sample has good density, and can make the current in the flash-sintering process pass through the inside of the sample as evenly as possible, thereby improving the sintering quality.

[0022] The present invention adopts flash firing technology to prepare plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic materials, thereby improving the plasticity of the antiferroelectric ceramic materials so that they can withstand greater volume stress and increase their charge and discharge life, thereby solving the problem of antiferroelectric ceramics failing under high electric fields (> turning point electric fields), improving energy storage density, and providing guidance for promoting the widespread application of antiferroelectric ceramics.

[0023] Beneficial effects: (1) The present invention flexibly controls the amount of Sr ions doped in the ceramic-based material to obtain an antiferroelectric material with high phase change electric field, low hysteresis, and high energy storage efficiency; it has a moderate dielectric constant, low dielectric loss, and excellent energy storage performance; (2) Compared with the prior art, the present invention adopts flash firing technology to regulate the composition and structural gradient of antiferroelectric ceramics, effectively reducing the sintering temperature and the holding time. The grain size becomes small and uniform through SEM and grain size characterization, and has high density; (3) Compared with the prior art, the present invention adopts flash firing technology to obtain dense ceramics with controllable composition structure gradient and fine and uniform grains; and the dislocation density is increased, the domain size is reduced, the average hardness and modulus are reduced, and plasticity is enhanced; (4) The preparation method of the present invention is simple and easy to operate, has low cost, low sintering temperature, saves energy, has short preparation time, good repeatability, and good practicality, and has very important application value for achieving plastic enhancement of antiferroelectric ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The dimensions of the sample obtained in Example 1 of the present invention and the schematic diagram of the conductive paste coating area; Figure 2 The cross-sectional SEM image of the antiferroelectric ceramic sample prepared in Example 1; Figure 3 The cross-sectional SEM image of the antiferroelectric ceramic sample prepared in Comparative Example 1; Figure 4 Schematic diagram of the dislocation structure and domain of the antiferroelectric ceramic sample prepared in Example 1; Figure 5 A schematic diagram of domains of the antiferroelectric ceramic sample prepared in Comparative Example 1; Figure 6 The charge and discharge curves of the antiferroelectric ceramic sample prepared in Example 1 under different test times; Figure 7 The charge and discharge curves of the antiferroelectric ceramic sample prepared in Comparative Example 1 under different test times; Figure 8 The dielectric temperature spectrum of the antiferroelectric ceramic sample prepared in Example 1; Fig. 9 The dielectric temperature spectrum of the antiferroelectric ceramic sample prepared in Comparative Example 1; Fig.10 The hysteresis loop of the antiferroelectric ceramic sample prepared in Example 1; Fig.11 The hysteresis loop of the antiferroelectric ceramic sample prepared in Comparative Example 1; Fig.12The ferroelectric hysteresis loop of the antiferroelectric ceramic sample prepared in Comparative Example 3; Fig.13 The ferroelectric hysteresis loop of the antiferroelectric ceramic sample prepared in Comparative Example 4. Specific embodiments

[0025] To further illustrate the content, features and actual effects of the present invention, the present invention will be described in detail below with reference to embodiments. It should be noted that the modified methods designed in the present invention are not limited to these specific embodiments. Without departing from the spirit and connotation of the design of the present invention, equivalent substitutions and modifications made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of protection required by the present invention. Unless otherwise specified, the percentage contents refer to mass percentage contents.

[0026] First, the present invention provides a lead lanthanum zirconate stannate titanate-based antiferroelectric ceramic with enhanced plasticity. The chemical formula of the lead lanthanum zirconate stannate titanate-based antiferroelectric ceramic is (Pb 0.975-x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3, where 0 < x ≤ 0.10. If the value of x is too large, the antiferroelectricity of the material will be weakened and the polarization intensity will be reduced; if the value of x is too small, the material matrix will exhibit a ferroelectric phase, which does not conform to the electrical performance characteristics of antiferroelectric materials.

[0027] Strontium ions have a smaller ionic radius and are equivalent substitutions, avoiding the additional effects caused by charge inhomogeneity, which is beneficial to directly and effectively regulate the stability of the antiferroelectric phase. Doping with strontium elements can improve the stability of the antiferroelectric phase, increase the transition electric field from the antiferroelectric phase to the ferroelectric phase, thereby increasing the energy storage density. In addition, doping with strontium ions can reduce the ferroelectric hysteresis, resulting in an increase in the energy storage efficiency.

[0028] In the present invention, the flash sintering technology can significantly reduce the grain size and increase the number of dislocations. The stress field and internal electric field around the dislocations will affect the crack propagation mode and can climb and decompose under the action of stress. Therefore, the local stress can be successfully relieved through dislocation slip or dislocation emission, reducing the average hardness and modulus of the sample, improving the plasticity of the sample, thereby inhibiting crack initiation and propagation, and achieving an extension of the charge-discharge life.

[0029] After theoretical research and multiple experimental verifications, the inventors found that there are dislocations inside lead-based antiferroelectric ceramics. Therefore, they hope to take advantage of the characteristics of the large number of dislocations in lead-based antiferroelectric ceramics and use dislocation slip or dislocation emission to alleviate the stress concentration caused by the antiferroelectric to ferroelectric phase transition, thereby improving its plasticity and inhibiting crack initiation and expansion. Based on this, the present invention creatively applies flash firing technology to lead zirconium tin titanate lanthanum-based antiferroelectric ceramic materials.

[0030] In the present invention, the plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic is prepared by combining solid phase synthesis with flash sintering technology. The preparation method of the plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic provided by the present invention is exemplarily described below.

[0031] Pb3O4 powder, La2O3 powder, SrCO3 powder, ZrO2 powder, TiO2 powder and SnO2 powder were selected as raw materials. 0.975-x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3 is weighed and mixed, and the mixture is ball-milled and dried to obtain a first ceramic powder.

[0032] In an optional embodiment, the ball milling method is wet ball milling, using zirconia balls as ball milling media and deionized water / anhydrous ethanol as ball milling agents, and ball milling is performed in a ratio of mixed powder: zirconia balls: water / anhydrous ethanol of 1: (3.5-5): (1.2-1.5), the ball milling speed is 120-180 r / min, and the ball milling time is 8-12 h.

[0033] The obtained ceramic powder is pressed into blocks and then calcined to obtain ceramic blocks.

[0034] In an optional embodiment, the pressure for pressing into blocks is 100-300 MPa, and the time is 5-30 seconds.

[0035] In an optional embodiment, the calcination parameters include: a calcination temperature of 800-900° C., a calcination time of 2-4 hours; and a calcination atmosphere of air.

[0036] The obtained ceramic block is ground and crushed, and then subjected to secondary ball milling, drying, and sieving. A binder is added to granulate the ceramic body, and the ceramic body is pressed and formed to obtain a ceramic body. The obtained ceramic body is aged and then ground and crushed for a secondary time to obtain a second ceramic powder.

[0037] In an optional embodiment, the secondary ball milling is performed by wet ball milling, using zirconia balls as the ball milling medium and deionized water / anhydrous ethanol as the ball milling agent. The ball milling is performed in a ratio of mixed powder: zirconia balls: water / anhydrous ethanol of 1: (3.5-5): (1.2-1.5), the ball milling speed is 120-180 r / min, and the ball milling time is 18-24 h.

[0038] In an optional embodiment, the binder is at least one of PVA and PVB; the concentration of the binder is 5-10wt% (for example, 7wt%); the amount of the binder added is 5-8wt% of the mass of the ceramic powder after sieving; preferably, the amount of the binder added is 5-6wt% of the mass of the ceramic powder after sieving.

[0039] In an optional embodiment, the diameter of the ceramic body is 8 to 12 cm, for example 10 cm.

[0040] In an optional embodiment, the aging temperature is room temperature and the time is 18 to 24 hours.

[0041] An appropriate amount of the second ceramic powder is taken and pressed to obtain a first green blank; the first green blank is sealed and then cold isostatically pressed and molded to obtain a second green blank.

[0042] In an optional embodiment, the mass of the second ceramic powder is 2.5-3.2 g.

[0043] In an optional embodiment, the first blank is cylindrical, with a diameter of 6 mm and a length of 1.6 to 2.4 cm.

[0044] In an optional embodiment, the pressure of the compression molding is 50-200 MPa, and the time is 3-10 seconds. The pressure of the cold isostatic pressing is 200-300 MPa (for example, 200 MPa), and the time is 3-5 minutes. The temperature of the plastic removal is 650-800°C, and the time is 2-3 hours.

[0045] The plasticity-enhanced zirconium tin titanate lead lanthanum-based antiferroelectric ceramic is prepared by sintering using flash sintering technology. Specifically, silver-palladium conductive paste is evenly coated on the two end regions of the obtained second blank, and after drying at 100-120°C, platinum wire is respectively wound around the two end regions of the coated electrode of the second blank, and placed in a flash sintering furnace; the two ends of the platinum wire are connected to the positive and negative poles of the DC power supply outside the furnace body, and an ammeter is connected in series in the circuit; first, the DC power supply adopts a voltage control mode, and the initial electric field strength is set to 100-300V / cm, and the furnace body heating rate is 5-15°C / min; when the current detector reading reaches the μA order of magnitude, the electric field strength is increased to 200-500V / cm; when the current density value reaches 10-30mA / mm 2After that, the DC power supply is switched to the current control mode; after maintaining a stable current density for 90 to 200 seconds in the current control mode, the DC power switch is turned off, and the flash furnace is taken out after being cooled to room temperature to obtain the plasticity-enhanced zirconium tin titanate lead lanthanum-based antiferroelectric ceramic.

[0046] The obtained plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramics were cut, processed, and sputtered with silver and gold electrodes in preparation for performance testing.

[0047] In an optional embodiment, the silver coating includes a printed electrode and a burned electrode; the temperature of the burned electrode is 700-800° C., and the time is 10-30 minutes.

[0048] In an optional embodiment, the obtained plasticity-enhanced lead lanthanum zirconium tin titanate-based antiferroelectric ceramic is cut and processed into thin sheets with a thickness of 0.1 to 1 mm.

[0049] The present invention utilizes flash firing technology to obtain dense ceramics with fine and uniform grains and enhanced plasticity at a relatively low temperature, and has low dielectric loss and high breakdown field strength. In addition, the plasticity of the antiferroelectric ceramic is significantly enhanced, and the enhancement amplitude can reach up to 15%, which is attributed to the changes such as reduced grain size, increased dislocation density and reduced domain shape brought about by the flash firing technology.

[0050] The mechanical properties of the obtained zirconium tin lead titanate lanthanum-based antiferroelectric ceramics were tested by nanoindentation method. The average hardness of the zirconium tin lead titanate lanthanum-based antiferroelectric ceramics was 6-7 MPa; the average modulus of the zirconium tin lead titanate lanthanum-based antiferroelectric ceramics was 160-170 MPa.

[0051] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0052] Example 1

[0053] In this embodiment 1, the lead zirconium tin titanate lanthanum-based antiferroelectric ceramic (Pb 0.975-x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3, wherein x=0.016) comprises: (1) Calculating the weight of each component in the powder raw material according to the above chemical formula and preparing according to the composition ratio, taking Pb3O4 (111.7718 g), La2O3 (1.6468 g), SrCO3 (1.1992 g), ZrO2 (31.1226 g), TiO2 (5.2647 g), SnO2 (28.2956 g), using wet ball milling at a speed of 120 r / min, mixing for 12 h to make the components uniform, and then drying to obtain the first ceramic powder; (2) pressing the obtained first ceramic powder into a block under a pressure of 150 MPa, and calcining it in an air atmosphere at a temperature of 900° C. for 2 hours to obtain a ceramic block; (3) The obtained ceramic block is ground and crushed, and then ball-milled for a second time for 24 hours. After the powder is dried and sieved, 6 wt% PVA (concentration is 7 wt%) is added, and the powder is fully mixed and pressed into a ceramic body with a diameter of about 10 cm; (4) aging the obtained ceramic body for 24 hours and then grinding and crushing it to obtain a second ceramic powder; (5) Weigh 3 g of the second ceramic powder and press it under a pressure of 80 MPa for 5 seconds to obtain a first elongated cylindrical green blank; after the first green blank is sealed, it is further cold isostatically pressed under a pressure of 200 MPa for 5 minutes; then the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is maintained for 2 hours to remove the plastic to obtain a second green blank with a diameter of φ = 6 mm and a length of L = 2 cm; (6) Evenly apply silver-palladium conductive paste on the 3mm area at both ends of the second blank, and dry it at 120°C; wrap platinum wire around the two end areas of the second blank coated with electrodes, and place it in a flash furnace; connect the two ends of the platinum wire to the positive and negative poles of the DC power supply outside the furnace, and connect a current detector in series in the circuit; first, the DC power supply adopts voltage control mode, sets the initial electric field strength to 100V / cm, and the furnace heating rate to 10°C / min; when the current reading reaches the μA level, increase the electric field strength to 150V / cm. When the current density reaches the preset value of 10.61mA / mm 2 After that, the DC power supply is switched to the current control mode; the DC power supply maintains a stable current density in the current control mode, and after the current is maintained for 150 seconds, the DC power switch is turned off, and the sample is taken out after the flash furnace cools to room temperature; (7) The samples were cut into thin sheets with a thickness of 1 mm (for dielectric property test) and 0.1 mm (for ferroelectric property test), and then sputtered with silver (silver burning temperature 750°C, insulation time 30 min) and gold electrodes as needed for dielectric and ferroelectric property tests.

[0054] Example 2

[0055] In this embodiment 2, the lead zirconium tin titanate lanthanum-based antiferroelectric ceramic (Pb 0.975-x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3, wherein x=0.064) comprises: (1) Calculate the weight of each component in the powder raw material according to the above chemical formula and prepare according to the composition ratio, take Pb3O4 (107.9969g), La2O3 (1.6745g), SrCO3 (4.8780g), ZrO2 (31.6470g), TiO2 (5.3534g), SnO2 (28.7724g), use wet ball milling method at 120r / min speed, mix for 12h, make the components evenly mixed, and obtain the first ceramic powder after drying; (2) pressing the obtained first ceramic powder into a block under a pressure of 150 MPa, and calcining it in an air atmosphere at a temperature of 900° C. for 2 hours to obtain a ceramic block; (3) The obtained ceramic block is ground and crushed, and then ball-milled for a second time for 24 hours. After the powder is dried and sieved, 6 wt% PVA (concentration is 7 wt%) is added, and the powder is fully mixed and pressed into a ceramic body with a diameter of about 10 cm; (4) aging the obtained ceramic body for 24 hours and then grinding and crushing it to obtain a second ceramic powder; (5) Weigh 3 g of the second ceramic powder and press it under a pressure of 80 MPa for 5 seconds to obtain a first elongated cylindrical green blank; after the first green blank is sealed, it is further cold isostatically pressed under a pressure of 200 MPa for 5 minutes; then the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is maintained for 2 hours to remove the plastic to obtain a second green blank with a diameter of φ = 6 mm and a length of L = 2 cm; (6) Evenly apply silver-palladium conductive paste on the 4mm area at both ends of the second blank, and dry it at 120°C; wrap platinum wire around the two end areas of the second blank coated with electrodes, and place it in a flash furnace; connect the two ends of the platinum wire to the positive and negative poles of the DC power supply outside the furnace, and connect a current detector in series in the circuit; first, the DC power supply adopts voltage control mode, sets the initial electric field strength to 100V / cm, and the furnace heating rate to 10°C / min; when the current reading reaches the μA level, increase the electric field strength to 150V / cm. When the current density reaches the preset value of 10.61mA / mm 2After that, the DC power supply is switched to the current control mode; the DC power supply maintains a stable current density in the current control mode, and after the current is maintained for 150 seconds, the DC power switch is turned off, and the sample is taken out after the flash furnace cools to room temperature; (7) The samples were cut into thin sheets with a thickness of 1 mm and 0.1 mm, and then sputtered with silver (silver burning temperature 750°C, holding time 30 min) and gold electrodes as needed for dielectric and ferroelectric properties testing.

[0056] Comparative Example 1

[0057] In this comparative example 1, the conventional method is used to sinter the lead zirconium tin titanate lanthanum-based antiferroelectric ceramic (Pb 0.975 - x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3, wherein x=0.016), comprising: (1) Calculating the weight of each component in the powder raw material according to the above chemical formula and preparing according to the composition ratio, taking Pb3O4 (111.7718 g), La2O3 (1.6468 g), SrCO3 (1.1992 g), ZrO2 (31.1226 g), TiO2 (5.2647 g), SnO2 (28.2956 g), using a wet ball milling method at a speed of 120 r / min, mixing for 12 h to make the components uniform, and then drying to obtain a first ceramic powder; (2) pressing the obtained first ceramic powder into a block under a pressure of 150 MPa, and calcining it in an air atmosphere at a temperature of 900° C. for 2 hours to obtain a ceramic block; (3) The obtained ceramic block is ground and crushed, and then ball-milled for a second time for 24 hours. After the powder is dried and sieved, 6 wt% PVA (concentration is 7 wt%) is added, and the powder is fully mixed and pressed into a ceramic body with a diameter of about 10 cm; (4) aging the obtained ceramic body for 24 hours and then grinding and crushing it to obtain a second ceramic powder; (5) Weigh 3 g of the second ceramic powder and press it under a pressure of 80 MPa for 5 seconds to obtain a first elongated cylindrical green blank; after the first green blank is sealed, it is further cold isostatically pressed under a pressure of 200 MPa for 5 minutes; then the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is maintained for 2 hours to remove the plastic to obtain a second green blank with a diameter of φ = 6 mm and a length of L = 2 cm; (6) placing the second green blank in an alumina crucible and covering it with a filler of the same component to prevent the volatilization of the lead component, covering the crucible with a lid and heating the temperature to 1320° C. at a rate of 2° C. / min, and keeping the temperature for 2 h to obtain an antiferroelectric ceramic material sintered by a conventional method; (7) The samples were cut and processed to a thickness of 1 mm and 0.1 mm, and then sputtered with silver (silver burning temperature 750°C, holding time 30 min) and gold electrodes as needed for dielectric and ferroelectric properties testing.

[0058] Comparative Example 2

[0059] In this comparative example 2, the conventional method was used to sinter the lead zirconium tin titanate lanthanum-based antiferroelectric ceramic (Pb 0.975 - x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3, wherein x=0.064), comprising: (1) Calculating the weight of each component in the powder raw material according to the above chemical formula and preparing according to the composition ratio, taking Pb3O4 (111.7718 g), La2O3 (1.6468 g), SrCO3 (1.1992 g), ZrO2 (31.1226 g), TiO2 (5.2647 g), SnO2 (28.2956 g), using wet ball milling at a speed of 120 r / min, mixing for 12 h to make the components uniform, and then drying to obtain the first ceramic powder; (2) pressing the obtained first ceramic powder into a block under a pressure of 150 MPa, and calcining it in an air atmosphere at a temperature of 900° C. for 2 hours to obtain a ceramic block; (3) The obtained ceramic block is ground and crushed, and then ball-milled for a second time for 24 hours. After the powder is dried and sieved, 6 wt% PVA (concentration is 7 wt%) is added, and the powder is fully mixed and pressed into a ceramic body with a diameter of about 10 cm; (4) aging the obtained ceramic body for 24 hours and then grinding and crushing it to obtain a second ceramic powder; (5) Weigh 3 g of the second ceramic powder and press it under a pressure of 80 MPa for 5 seconds to obtain a first elongated cylindrical green blank; after the first green blank is sealed, it is further cold isostatically pressed under a pressure of 200 MPa for 5 minutes; then the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is maintained for 2 hours to remove the plastic to obtain a second green blank with a diameter of φ = 6 mm and a length of L = 2 cm; (6) placing the second green blank in an alumina crucible and covering it with a filler of the same component to prevent the volatilization of the lead component, covering the crucible with a lid and heating the temperature to 1320° C. at a rate of 2° C. / min, and keeping the temperature for 2 h to obtain an antiferroelectric ceramic material sintered by a conventional method; (7) The samples were cut and processed to a thickness of 1 mm and 0.1 mm, and then sputtered with silver (silver burning temperature was 750°C and holding time was 30 min) and gold electrodes as required for dielectric and ferroelectric properties testing.

[0060] Comparative Example 3

[0061] In this comparative example 3, the lead zirconium tin titanate lanthanum-based antiferroelectric ceramic (Pb 0.975-x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3, wherein x=0) comprises: (1) Calculate the weight of each component in the powder raw material according to the above chemical formula and prepare according to the composition ratio, take Pb3O4 (113.0025g), La2O3 (1.6377g), ZrO2 (30.9517g), TiO2 (5.2358g), SnO2 (28.1402g), use wet ball milling method at 120r / min speed, mix for 12h, make the components evenly mixed, and obtain the first ceramic powder after drying; (2) pressing the obtained first ceramic powder into a block under a pressure of 150 MPa, and calcining it in an air atmosphere at a temperature of 900° C. for 2 hours to obtain a ceramic block; (3) The obtained ceramic block is ground and crushed, and then ball-milled for a second time for 24 hours. After the powder is dried and sieved, 6 wt% PVA (concentration is 7 wt%) is added, and the powder is fully mixed and pressed into a ceramic body with a diameter of about 10 cm; (4) aging the obtained ceramic body for 24 hours and then grinding and crushing it to obtain a second ceramic powder; (5) Weigh 1.2 g of the second ceramic powder, press it under a pressure of 100 MPa, and hold it for 10 seconds to obtain a first disc-shaped green body; then heat it to 700° C. at a heating rate of 2° C. / min, and hold it for 2 hours to remove the plastic, to obtain a second green body with a diameter of φ=13 mm; (6) placing the second green blank in an alumina crucible and covering it with a filler of the same component to prevent the volatilization of the lead component, covering the crucible with a lid and heating the temperature to 1320° C. at a rate of 2° C. / min, and keeping the temperature for 2 h to obtain an antiferroelectric ceramic material sintered by a conventional method; (7) The samples were processed to a thickness of 1 mm and 0.1 mm, and were sputtered with silver (silver burning temperature was 750°C, and the holding time was 30 min) and gold electrodes as required for testing of dielectric and ferroelectric properties.

[0062] Comparative Example 4

[0063] In this comparative example 4, the lead zirconium tin titanate lanthanum-based antiferroelectric ceramic (Pb 0.975-x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3, wherein x=0.12) comprises: (1) Calculate the weight of each component in the powder raw material according to the above chemical formula and prepare according to the composition ratio, take Pb3O4 (103.4289g), La2O3 (1.7081g), SrCO3 (9.3297g), ZrO2 (32.2816g), TiO2 (5.4608g), SnO2 (29.3492g), use wet ball milling method at 120r / min speed, mix for 12h, make the components evenly mixed, and obtain the first ceramic powder after drying; (2) pressing the obtained first ceramic powder into a block under a pressure of 150 MPa, and calcining it in an air atmosphere at a temperature of 900° C. for 2 hours to obtain a ceramic block; (3) The obtained ceramic block is ground and crushed, and then ball-milled for a second time for 24 hours. After the powder is dried and sieved, 6 wt% PVA (concentration is 7 wt%) is added, and the powder is fully mixed and pressed into a ceramic body with a diameter of about 10 cm; (4) aging the obtained ceramic body for 24 hours and then grinding and crushing it to obtain a second ceramic powder; (5) Weigh 1.2 g of the second ceramic powder, press it under a pressure of 100 MPa, and hold it for 10 seconds to obtain a first disc-shaped green body; then heat it to 700° C. at a heating rate of 2° C. / min, and hold it for 2 hours to remove the plastic, to obtain a second green body with a diameter of φ=13 mm; (6) placing the second green blank in an alumina crucible and covering it with a filler of the same component to prevent the volatilization of the lead component, covering the crucible with a lid and heating the temperature to 1320° C. at a rate of 2° C. / min, and keeping the temperature for 2 h to obtain an antiferroelectric ceramic material sintered by a conventional method; (7) The samples were processed to a thickness of 1 mm and 0.1 mm, and were sputtered with silver (silver burning temperature was 750°C, and the holding time was 30 min) and gold electrodes as required for testing of dielectric and ferroelectric properties.

[0064] The samples prepared in Examples 1-2 and Comparative Examples 1-2 were subjected to nanoindentation mechanical property tests, and the test conditions were: maximum indentation depth of 2000 nm, surface indentation speed of 10 nm / s, and holding time of 10 s. Table 1 lists the mechanical properties of the samples prepared in Examples 1-2 and Comparative Examples 1-2 of the present invention.

[0065] Table 1: Average hardness (MPa) Average modulus (MPa) Example 1 6.397 163.3 Example 2 6.763 174.2 Comparative Example 1 7.530 183.4 Comparative Example 2 6.915 176.3 .

[0066] As shown in Table 1, the average hardness and modulus of the ceramic samples obtained by the preparation method of the present invention are both lower than those of the comparative examples. Compared with comparative example 1, the average hardness and modulus of Example 1 are reduced by 15.0% and 11.0%, respectively, and the average hardness and modulus of Example 2 are reduced by 1.77% and 1.19%, respectively, compared with comparative example 2. This indicates that the present invention uses flash firing technology to improve the plasticity of antiferroelectric ceramics.

[0067] Dielectric temperature spectrum and hysteresis loop test at 250 kV / cm of samples prepared in Examples 1-2 and Comparative Examples 1-4 Table 2 lists the dielectric properties and ferroelectric properties of the samples prepared in Examples 1-2 and Comparative Examples 1-4 of the present invention.

[0068] Table 2:

[0069] As can be seen from Table 2, the room temperature dielectric constant and Curie temperature of the ceramic samples of the embodiments (Examples 1-2) obtained by the preparation method of the present invention are basically consistent with the comparative examples (Comparative Examples 1-2) of the same components. However, the forward turning electric field of the embodiment (Example 1-2) is significantly improved compared with the comparative example (Comparative Example 1-2) of the same components. This also contributes to the improvement of its energy storage density and energy storage efficiency. Therefore, under the same components and the same test conditions, the energy storage efficiency of the embodiment (Example 1-2) is increased compared with the comparative example (Comparative Example 1-2). Comparative Examples 1-4 correspond to ceramic samples with different Sr contents of traditional sintering, respectively. When the strontium content is 0, the room temperature dielectric constant and Curie temperature of Comparative Example 3 are both high, and the energy storage density and energy storage efficiency are both low. With the increase of Sr content, the room temperature dielectric constant and Curie temperature of the ceramic sample decrease, while the energy storage density, energy storage efficiency and forward turning electric field increase. However, when the strontium content is too high (x=0.12), the room temperature dielectric constant and Curie temperature of Comparative Example 4 are relatively low. This indicates that the Sr content needs to be controlled within a suitable range to ensure the excellent comprehensive performance of the ceramic material of this system.

[0070] Figure 2 and Figure 3The cross-sectional SEM images of the antiferroelectric ceramic samples prepared in Example 1 and Comparative Example 1 are shown respectively. As can be seen from the figure, a dense ceramic sample was successfully prepared by the flash sintering technology, and the grain size was reduced compared with the traditional sintering.

[0071] Figure 4 Schematic diagram of the dislocation structure and domain of the antiferroelectric ceramic sample prepared in Example 1; Figure 5 Schematic diagram of the domains of the antiferroelectric ceramic sample prepared in Comparative Example 1. Figure 4 It can be seen that the number of dislocations (black short lines in the figure) in the flash-burned sample of Example 1 has increased. Dislocations, as nucleation points of domains, also affect the shape of domains. The domain shape in the flash-burned sample is a blocky domain of smaller size, with a size order of magnitude of hundreds of nanometers. Figure 5 It can be seen that no obvious dislocation structure appears in the antiferroelectric ceramic sample prepared by the conventional method in Comparative Example 1, and the domain shape is a classic long strip layered domain, and the domain size is larger than that of the flash fired sample. It can be seen that after flash firing, the changes in the microstructure of the ceramic sample achieve the beneficial effects of the present invention.

[0072] Figure 6 and Figure 7 The charge and discharge curves of the antiferroelectric ceramic samples prepared in Example 1 and Comparative Example 1 at different test times respectively indicate the change of the discharge current with the discharge time during the discharge process of the samples. As can be seen from the figure, the complete discharge interval of Comparative Example 1 and Example 1 is 500-800ns, and the discharge cycle is about 300ns. Under an electric field of 30kV / cm, the charge and discharge times of the ceramic sample of Example 1 can reach more than 4200 times, while the charge and discharge times of the ceramic sample of Comparative Example 1 is only more than 350 times. And the discharge current of Example 1 is slightly increased. It shows that the charge and discharge life can be extended by improving the plasticity.

[0073] Figure 8 and Fig. 9 The dielectric temperature spectra of the antiferroelectric ceramic samples prepared in Example 1 and Comparative Example 1 respectively show the variation trend of the dielectric constant and loss tangent with temperature. As can be seen from the figure, the dielectric constant value at room temperature in Example 1 is 1145, and the Curie temperature is 137°C; the room temperature dielectric constant value of Comparative Example 1 is 1148, and the Curie temperature is 136°C. The variation trend of the dielectric constant of Example 1 with temperature is more gentle than that of Comparative Example 1, and the sharpness of the Curie peak is reduced.

[0074] Fig.10 and Fig.11The hysteresis loops of the antiferroelectric ceramic samples prepared in Example 1 and Comparative Example 1 respectively represent the changes of polarization intensity and current with electric field. As can be seen from the figure, both Example 1 and Comparative Example 1 have sharp double current peaks, indicating that both have obvious strong antiferroelectric properties. The forward turning electric field (electric field corresponding to the positive current peak) of Example 1 is 37.6kV / cm, which is an increase compared to 34.9kV / cm of Comparative Example 1, which is beneficial to the improvement of its energy storage density.

[0075] Fig.12 and Fig.13 The hysteresis loops of the antiferroelectric ceramic samples prepared in Comparative Examples 3 and 4 are shown in Figure 3. As can be seen from the figure, when no strontium is doped (Comparative Example 3), only a complete current peak is shown, and the residual polarization intensity is large, indicating that it is in the ferroelectric phase and cannot exert the high energy storage density characteristics of antiferroelectric materials. When the strontium element is doped too much (Comparative Example 4), the current peak becomes gentle, indicating that the antiferroelectricity of the material is weakened and the polarization intensity decreases significantly.

Claims

1. A plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic, characterized in that: The chemical formula of the lead lanthanum zirconate stannate antiferroelectric ceramic is (Pb 0.975-x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3, where 0 < x ≤ 0.10; the plastic-enhanced lead lanthanum zirconate stannate antiferroelectric ceramic is prepared by flash sintering technology; wherein, the initial electric field strength is set to 100-300 V / cm, and the heating rate of the flash furnace body is 5-15 °C / min; when the reading of the current detector reaches the μA order of magnitude, the electric field strength is increased to 200-500 V / cm; when the current density value reaches 10-30 mA / mm 2 2, maintain a stable current density for 90-200 s; Preferably, the flash furnace heating rate is 8-12°C / min.

2. The lead zirconium tin titanate lanthanum-based antiferroelectric ceramic according to claim 1, characterized in that: Set the initial electric field strength to 100-150 V / cm. When the current detector reading reaches the μA level, increase the electric field strength to 200-300 V / cm.

3. The lead zirconium tin titanate lanthanum based antiferroelectric ceramic according to claim 1 or 2, characterized in that: The average hardness of the lead zirconium tin titanate lanthanum-based antiferroelectric ceramic is 6-7 MPa; the average modulus of the lead zirconium tin titanate lanthanum-based antiferroelectric ceramic is 160-175 MPa.

4. A method for preparing lead zirconium tin titanate lanthanum-based antiferroelectric ceramics according to any one of claims 1 to 3, characterized in that: include: (1) Pb3O4 powder, La2O3 powder, SrCO3 powder, ZrO2 powder, TiO2 powder and SnO2 powder were used as raw materials and the chemical formula (Pb 0.975-x La 0.02 Sr x )(Zr 0.5 Sn 0.37 Ti 0.13 ) 0.9975 O3 is weighed and mixed, ball-milled and dried to obtain a first ceramic powder; (2) pressing the obtained ceramic powder into blocks, and calcining to obtain ceramic blocks; (3) grinding and crushing the obtained ceramic block, performing secondary ball milling, drying, and screening, adding a binder to granulate, and pressing to obtain a ceramic body; aging the obtained ceramic body, and then performing secondary grinding and crushing to obtain a second ceramic powder; (4) taking an appropriate amount of the second ceramic powder and pressing and molding it to obtain a first green blank; sealing the obtained first green blank and then cold isostatically pressing and removing the plastic to obtain a second green blank; (5) The plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic is prepared by sintering using a flash sintering technique.

5. The preparation method according to claim 4, characterized in that: In step (1), the ball milling method is wet ball milling, with zirconium oxide balls as ball milling media, deionized water / anhydrous ethanol as ball milling agents, and the ball milling is carried out in a ratio of mixed powder: zirconium oxide balls: water / anhydrous ethanol of 1: (3.5-5): (1.2-1.5), the ball milling speed is 120-180 r / min, and the ball milling time is 8-12 h.

6. The preparation method according to claim 4 or 5, characterized in that: In step (2), the pressure for pressing into blocks is 100 to 300 MPa, and the time is 5 to 30 seconds; The calcination temperature is 800-900° C., the calcination time is 2-4 hours, and the ambient atmosphere is air.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (3), the secondary ball milling is performed by wet ball milling, using zirconium oxide balls as the ball milling medium and deionized water / anhydrous ethanol as the ball milling agent, and the ball milling is performed in a ratio of mixed powder: zirconium oxide balls: water / anhydrous ethanol of 1: (3.5-5): (1.2-1.5), the ball milling speed is 120-180 r / min, and the ball milling time is 18-24 h; The binder is at least one of PVA and PVB; the concentration of the binder is 5-10wt%; the amount of the binder added is 5-8wt% of the mass of the sieved ceramic powder; The aging temperature is room temperature and the aging time is 18 to 24 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (4), the mass of the second ceramic powder is 2.5 to 3.2 g; The compression molding pressure is 50-200 MPa and the time is 3-10 s; The cold isostatic pressing pressure is 200-300 MPa and the time is 3-5 min; The temperature of the plastic removal is 650-800° C., and the time is 2-3 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (5), the flash firing technology includes: uniformly coating the two end regions of the obtained second blank with silver-palladium conductive paste, drying at 100-120°C, and winding the two end regions of the second blank coated with electrodes with platinum wire respectively, and placing them in a flash firing furnace; preferably, the width of the silver-palladium conductive paste coated on the two end regions of the second blank is 3-5 mm.

10. The preparation method according to any one of claims 4 to 9, characterized in that: The preparation method further comprises: cutting, processing, and sputtering the obtained plasticity-enhanced lead zirconium tin titanate lanthanum-based antiferroelectric ceramic with silver and gold electrodes.

Citation Information

Patent Citations

  • Anti-ferroelectric energy storage ceramic material and preparation method thereof

    CN103641477A

  • Preparation method of sintering zirconium-aluminum composite eutectic ceramic through flash sintering technology

    CN107188544A

  • Lead lanthanum zirconate stannate antiferroelectric ceramic as well as preparation method and application thereof

    CN111393149A

  • Strontium-doped lead lanthanum zirconate stannate titanate relaxed anti-ferroelectric thick-film ceramic as well as preparation method and application thereof

    CN111470863A

  • High-energy-storage-density low-titanium lead zirconate-based antiferroelectric ceramic and preparation method thereof

    CN111548154A

Cited By

  • Lead zirconate-based antiferroelectric ceramic as well as preparation method and application thereof

    CN120965320A

  • A lead zirconate-based antiferroelectric ceramic, a preparation method and applications thereof

    CN120965320B